Seeking synergies: understanding the evidence that links menstrual health and sexual and reproductive health and rights. Issue 1 (1st January 2021) - Wilson, Lucy C; Rademacher, Kate H; Rosenbaum, Julia; Callahan, Rebecca L; Nanda, Geeta; Fry, Sarah; Mackenzie, Amelia C L
ABSTRACT: Global efforts to improve menstrual health and sexual and reproductive health and rights (SRHR) are fundamentally intertwined and share similar goals for improving health and well-being and increasing gender equality. Historically, however, the two fields have operated independently and missed opportunities to build upon their biological and sociocultural linkages. Biological touchpoints connecting the two fields include genital tract infections, menstrual disorders, contraception, and menopause. From a sociocultural perspective, intersections occur in relation to the experience of puberty and menarche, gender norms and equity, education, gender-based violence, and transactional sex. We describe evidence linking menstrual health and SRHR and offer recommendations for integration that could strengthen the impact of both fields.